2021
DOI: 10.1186/s12957-021-02318-y
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy combined with radical surgery for stage IB2/IIA2 cervical squamous cell carcinoma: a prospective, randomized controlled study of 35 patients

Abstract: Objective This study aimed to evaluate the clinical outcomes for patients with stage IB2/IIA2 cervical squamous cell carcinoma treated with neoadjuvant chemotherapy combined with radical surgery. Methods A total of 68 patients with cervical squamous cell carcinoma were randomly divided into the experimental group (n = 35) and the control group (n = 33). The patients in the experimental group received paclitaxel plus cisplatin neoadjuvant chemothera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…In the implementation of comprehensive treatment for cervical cancer patients, the clinical approach mostly adopts staged treatment. That is, cervical cancer patients with stage Ia1–IIa2 are treated with comprehensive treatment measures mainly with surgery and supplemented with radiotherapy; patients with stage ≥IIb are treated with simultaneous radiotherapy and chemotherapy with radiotherapy as the core ( 7 , 11 ). However, it has been observed that after cervical cancer surgery, the sense of experience such as pain or incompleteness caused by surgical resection can lead to a range of negative emotions such as low self-esteem, loss, and depression ( 12 , 13 ); Damage to adjacent organs, fatigue or bone marrow suppression caused by radiotherapy can cause further damage to the patient's health status and quality of life ( 14 , 15 ); Moreover, the damage to the digestive tract caused by chemotherapy can lead to decreased appetite, nausea and vomiting, and even rejection of food, and the patient's nutrient intake is insufficient, and the body's immunity can be further reduced ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the implementation of comprehensive treatment for cervical cancer patients, the clinical approach mostly adopts staged treatment. That is, cervical cancer patients with stage Ia1–IIa2 are treated with comprehensive treatment measures mainly with surgery and supplemented with radiotherapy; patients with stage ≥IIb are treated with simultaneous radiotherapy and chemotherapy with radiotherapy as the core ( 7 , 11 ). However, it has been observed that after cervical cancer surgery, the sense of experience such as pain or incompleteness caused by surgical resection can lead to a range of negative emotions such as low self-esteem, loss, and depression ( 12 , 13 ); Damage to adjacent organs, fatigue or bone marrow suppression caused by radiotherapy can cause further damage to the patient's health status and quality of life ( 14 , 15 ); Moreover, the damage to the digestive tract caused by chemotherapy can lead to decreased appetite, nausea and vomiting, and even rejection of food, and the patient's nutrient intake is insufficient, and the body's immunity can be further reduced ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive treatment plan based on surgery and radiotherapy, supplemented by chemotherapy, is usually adopted clinically after considering the patient's age, physical condition, fertility needs, and cancer stage. However, there is a high risk of complications such as pain, radiation cystitis, radiation proctitis, bone marrow suppression, skin damage, hair loss, and gastrointestinal symptoms after surgery or during radiotherapy or chemotherapy, which affects patients' physical and mental status and treatment compliance ( 6 , 7 ). However, the lack of scientific medical guidance and standardized nursing management after patients leave the hospital makes them more prone to a series of near and long-term complications and sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…В ряде публикаций авторы сообщают, что внутриартериальное введение лекарственных препаратов способствует более высокой частоте клинического ответа, чем при внутривенной химиотерапии, что, в свою очередь, приводит к более благоприятному прогнозу выживаемости [13]. В то же время существуют исследования, указывающие, что проведение НАХТ не влияет на безрецидивную и общую выживаемость по сравнению с пациентками, не получавшими химиотерапию на первом этапе, но в то же время способствует уменьшению параметральной инфильтрации, глубине стромальной инвазии, снижению частоты использования послеоперационной лучевой терапии [14]. Многоцентровое исследование, включавшее больных РШМ IB/ IIA стадии, показывает, что НАХТ была связана с относительным снижением кровопотери, увеличением времени операции и повышением вероятности применения лапароскопической хирургии.…”
Section: результаты и обсуждениеunclassified
“…An alternative to this treatment approach is radical hysterectomy (RH), which can improve patients' survival outcomes and maintain primitive postoperative pathological state [14]. Intermediate-risk factors, including large tumor diameter >4 cm, lymphovascular space invasion (LVSI) and deep stromal infiltration, and highrisk factors, such as lymph node metastasis (LNM), positive parametria and positive surgical margin, have a significant impact on the recurrence of LACC [15].…”
Section: Introductionmentioning
confidence: 99%